Thomas Blake account book - Blake, Thomas, active 1782-1783.
Account book of receipts kept by Blake, paymaster to the First New Hampshire Regiment.
Army officer.
Collection material in English.
Keywords: United States. -- Continental Army. -- New Hampshire Regiment, First; United States -- History -- Revolution, 1775-1783.; Army officers